1979
DOI: 10.1002/mpo.2950070105
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival in childhood acute leukemia: “Late” relapses

Abstract: The "late" relapse patterns of childhood acute leukemia were studied in 83 children in their first continuous complete remission for more than three years prior to randomization for stopping therapy (40 patients) or continuing therapy (43 patients) for a total of six years. Twenty of 83 (22.9%) have relapsed: Ten in the bone marrow, one in the central nervous system, and nine in the testes. The testes relapse rate of 41.1% (7/17) in males discontinuing therapy at three years was much higher than that of 8.7% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In concyclical use of doxorubicin in the first year, the use of trast, others have reported a much higher incidence of maintenance doses of intrathecal methotrexate, and treat-testicular relapse following treatment with protocols that ment with pulses of vincristine, methotrexate, 6-mercap-did not include anthracycline induction therapy topurine, and prednisone during continuation therapy. [ 18,21,22]. The overall FFS results were comparable to those of Is late testicular relapse responsible for the poorer other studies conducted at the same time [1,3,12-141 but outcome in males in our VP induction group as suggested were better for patients who received VPA induction.…”
Section: Discussionsupporting
confidence: 86%
“…In concyclical use of doxorubicin in the first year, the use of trast, others have reported a much higher incidence of maintenance doses of intrathecal methotrexate, and treat-testicular relapse following treatment with protocols that ment with pulses of vincristine, methotrexate, 6-mercap-did not include anthracycline induction therapy topurine, and prednisone during continuation therapy. [ 18,21,22]. The overall FFS results were comparable to those of Is late testicular relapse responsible for the poorer other studies conducted at the same time [1,3,12-141 but outcome in males in our VP induction group as suggested were better for patients who received VPA induction.…”
Section: Discussionsupporting
confidence: 86%
“…The possible influence of the length of maintenance therapy on the rates of ITR has been studied by at least three groups [21,30,31]. In the MRC trials (UKALL I-111) patients were randomized in groups receiving 1 'h to 2 years or 3 years maintenance therapy.…”
Section: Disc Usslo Nmentioning
confidence: 99%
“…In this sense, routine testicular biopsies performed at 2 years' remission may help to identify a group of patients with high risk of late relapse. The review of the reported studies [19,20,23,31] shows that the overall rate of subsequent marrow or CNS relapses for patients with positive biopsies was 50% (21 out of 42 patients), which was significantly higher than the 16% (38 out of 229) for patients with negative biopsies. Consequently, we think that the practice of routine testes biopsy, employing new techniques with cell markers [32], maintains its value in detecting residual disease, at least until more effective therapies show that incidence of occult infiltrates is irrelevant.…”
Section: Disc Usslo Nmentioning
confidence: 99%
“…2,3,8,12 About 10 per cent of these patients have occult leukemic infiltration to the testes. 2,3,12 This patient had isolated testicular relapse 5 years after completing chemotherapy for ALL. In two large series of children having chemotherapy discontinued after 2.5 years or more of continuous remission maintenance therapy, none of them had bone marrow or extramedullary relapse 4.5 years after completing therapy.…”
Section: Discussionmentioning
confidence: 96%
“…1-3 Some of these patients will eventually relapse, with most recurring during the first year after discontinuation of therapy. [1][2][3] Extramedullary relapse may occur while the patient is still undergoing chemotherapy or after it has been discontinued. Since the introduction of CNS sanctuary therapy, leukemic infiltration of the testis has emerged as a more common site of extramedullary relapse in boys.…”
mentioning
confidence: 99%